(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The deterioration of the environment, alterations in climate, and the decline of biodiversity have prompted significant global apprehensions, particularly highlighted by the United Nations’ Sustainable Development Goals (SDGs). Specifically, SDG 14 (Life Below Water) and SDG 15 (Life on Land) underscore the imperative to safeguard both aquatic and terrestrial ecosystems. Within Christian theology, stewardship is perceived as a divine obligation, wherein humanity is charged with the responsibility of nurturing and conserving God’s creation. Nevertheless, human actions persist in damaging natural resources, thereby jeopardizing sustainability and contravening scriptural tenets of care and justice. This research seeks to investigate the concept of Christian stewardship regarding divinely entrusted natural resources through a biblical lens, assessing the congruence of this theological framework with the objectives of Sustainable Development Goals 14 and 15, which emphasize sustainability and environmental accountability. The methodology employed includes a qualitative and theological approach, featuring Scriptural Exegesis of significant biblical passages (such as Genesis 1:26–30 and Psalm 24:1) to derive theological tenets of stewardship, a Literature Review of Christian environmental ethics alongside sustainable development frameworks, and a Comparative Analysis of biblical stewardship doctrines in relation to the targets set forth by SDGs 14 and 15. The research revealed a significant theological foundation for environmental stewardship within Christian teachings. The concept of biblical stewardship extends beyond mere dominion; it encompasses responsible guardianship, accountability, and sustainability. This perspective aligns closely with the objectives of Sustainable Development Goals 14 and 15, particularly in fostering biodiversity, minimizing pollution, and safeguarding habitats. Additionally, numerous faith-based organizations are already engaged in conservation efforts motivated by their religious beliefs. In conclusion, Christian stewardship offers a moral and spiritual framework that enhances scientific and policy-oriented strategies for sustainable development. The biblical imperative to care for creation resonates with fundamental values shared by the SDGs, including justice, sustainability, and intergenerational responsibility. It is recommended that faith communities increase their participation in environmental advocacy and education. Churches should incorporate environmental stewardship into their teachings and practices. Furthermore, collaborations among religious organizations, governmental bodies, and NGOs should be strengthened to promote the advancement of SDGs 14 and 15. Future research should investigate the effects of faith-based environmental initiatives on both local and global sustainability outcomes.